2014
DOI: 10.1093/applin/amu006
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Individual Differences in L2 Narrative Production: The Contribution of Input, Processing, and Output Anxiety

Abstract: The aim of this study was to investigate the effects of cognitive task complexity and individual differences in input, processing, and output anxiety (IPOA) on L2 narrative production. The participants were enrolled in a bilingual secondary educational program. They performed two narrative tasks in speech and writing. The participants’ level of anxiety was assessed using the IPOA scale (MacIntyre and Gardner 1994). The results demonstrate that spoken and written modalities are influenced differently by anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…However, controversies exist regarding the role of negative activating emotions such as anxiety, guilt and shame (Marcos-Llinás and Garau, 2009;Teimouri, 2018;. As for anxiety, researchers reported contradictory results in terms of whether anxiety exerts a debilitating effect (Oya et al, 2004;Shao et al, 2013;, a facilitating effect (Marcos-Llinás and Garau, 2009;Trebits, 2016), or no effect on L2 achievement (In'nami, 2006). Zhang's (2019) meta-analysis showed that anxiety was overall negatively correlated with L2 performance and that the controversies among previous studies may be explained by the moderator variables such as the anxiety type, age, and lexical similarity.…”
Section: Achievement Emotions In Second Language Acquisitionmentioning
confidence: 99%
“…However, controversies exist regarding the role of negative activating emotions such as anxiety, guilt and shame (Marcos-Llinás and Garau, 2009;Teimouri, 2018;. As for anxiety, researchers reported contradictory results in terms of whether anxiety exerts a debilitating effect (Oya et al, 2004;Shao et al, 2013;, a facilitating effect (Marcos-Llinás and Garau, 2009;Trebits, 2016), or no effect on L2 achievement (In'nami, 2006). Zhang's (2019) meta-analysis showed that anxiety was overall negatively correlated with L2 performance and that the controversies among previous studies may be explained by the moderator variables such as the anxiety type, age, and lexical similarity.…”
Section: Achievement Emotions In Second Language Acquisitionmentioning
confidence: 99%
“…Each measure of syntactic complexity was useful for capturing language development since the best‐fitting model for each measure showed a significant and meaningful increase in complexity in the speeches over time. Complexity, particularly in speech, is expected to be retarded by limitations in cognitive load (Trebits, ); these results suggest that with increasing proficiency, cognitive resources are available for complexifying the language performance. There was no decrease or plateau in any type of complexity (such as subordination) in these data, echoing De Clercq and Housen's () findings, despite expectations about the development of syntactic complexity (e.g., Lambert & Kormos, ; Norris & Ortega, ).…”
Section: Resultsmentioning
confidence: 99%
“…Production modality (written or spoken) in particular influences syntactic complexity because speakers must plan and monitor their language production simultaneously, and the additional cognitive load might hinder or delay learners from producing complex oral language (Trebits, ). The ephemeral nature of speech (for both the speaker and the listener) may also discourage integration of ideas into multi‐clause utterances in speech (Schiffrin, ).…”
Section: Introductionmentioning
confidence: 99%
“…International Journal of Social Sciences and Humanities Invention, vol. 09, Issue 02, February 2022 Trebits (2014) claimed that output anxiety has a considerable and robust link with students' speaking skills. The learners' output is similarly affected by input and processing anxiety.…”
Section: Literaure Reviewmentioning
confidence: 99%
“…It is strongly reliant on an individual's memory capacity to store and process the input. Trebits (2014) postulates that learners are more anxious when decoding spoken processes than translating textual modalities. According to Jugo's (2020) results, Filipino learners express a substantial level of anxiety when encoding an external message, and speaking activities are negative predictors.…”
Section: Data Analysesmentioning
confidence: 99%